Attrition and associated factors among patients on chronic antihypertensive therapy at Mulago hospital, Uganda: A mixed method study - Nathan Ntenkaire; Mark Kaddu Mukasa; Patience Muwanguzi; Brian Mikka; Sandra Lunkuse; Julius Mubiru; Maxwell Okwero; Beatrice Basuuta; Douglas Bulafu; Joan N. Kalyango (PLoS ONE, 2026)
Background Attrition among patients on chronic antihypertensive therapy is a significant problem that can lead to serious health consequences, including uncontrolled blood pressure. Several factors underlie attrition, so healthcare providers must address them to prevent treatment discontinuation and ensure optimal outcomes. Therefore, this study assessed attrition and associated factors among hypertensive patients from January 2020 and December 2022. Methods A sequential explanatory mixed-methods design. The quantitative study was a retrospective cohort study design using files of 1215 hypertensive patients. The qualitative study employed an explanatory descriptive design among 16 patients. A data abstraction tool and an interview guide were used for data collection. Attrition was defined as patients who were lost to follow-up. Extended Cox regression was used to determine the factors associated with time to attrition at 5% level of significance and qualitative data analysis employed a thematic analysis codebook. Results The attrition proportion was 56.8% (95% confidence interval (CI) 54.0–59.7) with most patients getting lost to follow-up in 2020 (64.9%) and fewest in 2021 (54.7%). Age (hazard ratio (HR)=0.947, 95% CI 0.931–0.963), female Sex (HR = 0.734, 95% CI 0.620–0.869), residence outside Kampala (Capital City) (HR = 1.24, 95%CI 1.063–1.455), 2022 cohort entry year (HR = 1.433, 95% CI 1.156–1.777), last visit systolic blood pressure (SBP) (HR = 1.014, 95% CI 1.009–1.018), and last visit diastolic blood pressure (DBP) (HR = 0.947,95% CI 0.931–0.963) were associated with time to attrition. Loss to follow-up (LTFU) was driven by structural and contextual barriers, health system challenges, and illness perceptions and health-related limitations. Conclusion Hypertensive patient attrition proportion is high, below the Centers for Disease Control and Prevention’s 80% retention target. This calls for innovative retention strategies, and targeted support for high-risk groups like the male patients and those distant from the health facility. Patient-centered approaches addressing structural and health system barriers are essential to improving retention in hypertension care.